2012
DOI: 10.1097/fpc.0b013e3283544043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of single nucleotide polymorphisms and biological pathways associated with response to TNFα inhibitors in patients with rheumatoid arthritis

Abstract: In a genome-wide association study of 196 genetically homogenous Danish patients with RA and in a meta-analysis, we found no SNPs associated with treatment response to TNFα inhibitors. A GSEA suggested that the transforming growth factor β, TNF, mitogen-activated protein kinase, and mammalian target of rapamycin pathways may be associated with treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 44 publications
3
53
3
Order By: Relevance
“…We did not find any evidence for association for the loci identified from previously published GWAS on anti-TNF response [18][19][20] or for the PTPRC gene (table 3) 16 17 in the Dutch patients included in our stage 1 GWAS, suggesting that these genes do not play a major role in anti-TNF treatment outcome in our population. However, the power of our study to detect an association with PTPRC loci at p<0.0005 in a set size of 882 patients was 26%.…”
Section: Figurementioning
confidence: 53%
See 2 more Smart Citations
“…We did not find any evidence for association for the loci identified from previously published GWAS on anti-TNF response [18][19][20] or for the PTPRC gene (table 3) 16 17 in the Dutch patients included in our stage 1 GWAS, suggesting that these genes do not play a major role in anti-TNF treatment outcome in our population. However, the power of our study to detect an association with PTPRC loci at p<0.0005 in a set size of 882 patients was 26%.…”
Section: Figurementioning
confidence: 53%
“…16 17 A number of additional potential candidate loci have been suggested on the basis of results from three genome-wide association studies (GWAS). [18][19][20] In a GWAS of 566 patients with RA, Plant et al 19 found evidence of association at seven genetic loci with response to TNF blockade, two of which mapped within genes: PDZ domain-containing protein 2 (PDZD2) and eyes absent homologue 4 (EYA4). In a small study (n=89) by Liu et al, 18 association was reported for markers in the MAFB and PON1 gene regions as well as in a region of chromosome 9 that contains the interferon kappa (IFN-κ), MOBKL2B and C9orf72 loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a genome-wide association studies of anti-TNF response in rheumatoid arthritis in the Danish population identified a large group of candidate regions. 17 Using an independent cohort of rheumatoid arthritis patients from the Spanish population, we were able to replicate the association between PDE3A-SLCO1C1 (phosphodiesterase 3A-SoLute Carrier Organic anion transporter family member 1C1) locus on chromosome 12p12.2 and anti-TNF response. 18 Combining the evidence between the two patient cohorts, PDE3A-SLCO1C1 association was the first pharmacogenetic locus to reach the genome-wide level of significance in rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 82%
“…8 It was replicated in the first genomewide association study (GWAS) of response to TNFi, 9 but not in subsequent GWAS on this phenotype. [10][11][12][13] The second replicated biomarker, in the PTPRC gene, was identified in a study considering the RA susceptibility loci as candidate genes. 14 The RA risk allele of this locus was associated with improved response to TNFi.…”
Section: Introductionmentioning
confidence: 99%